The Effect of Chronic Anticoagulation on Early Postoperative Outcomes Following Total Knee Arthroplasty: A TriNetX Database Study - Andrea H. Johnson, MSN CRNP; Jane C. Brennan, MS; Shawn S. Simpson, PA-C; Justin J. Turcotte, PhD MBA; Paul J. King, MD (Arthroplasty Today, 2025)
Background: Medications used for pharmacologic venous thromboembolism prophylaxis are associated with postoperative complications including bleeding, wound complications, and infection. These same medications are used for chronic anticoagulation, and little research has been done on total knee arthroplasty (TKA) complications associated with these medications, particularly manipulation under anesthesia (MUA) and revision TKA. The purpose of this study is to evaluate the rate of MUA and other early postoperative complications in patients undergoing TKA with a preoperative history of chronic anticoagulation. Methods: The TriNetX database was retrospectively queried for all patients undergoing TKA with perioperative tranexamic acid. Patients were divided into cohorts by whether or not they had a history of chronic anticoagulant use and had an anticoagulant medication prescribed within 6 months of surgery. The cohorts were propensity score matched on demographic and comorbidity data; 7367 patients remained in each cohort after matching. Results: Patients with chronic anticoagulant use were 1.72 times more likely to undergo an MUA (odds ratio [OR]: 1.718, 95% confidence intervals [CI]: 1.403-2.104; P < .001), 1.32 times more likely to have a revision TKA (OR: 1.324, 95% CI: 1.006-1.742; P = .044), and were 1.53 times more likely to have wound disruption (OR: 1.530, 95% CI: 1.214-1.927; P < .001) within the 1-year postoperative period. Conclusions: Patients undergoing TKA while on chronic anticoagulation have worse outcomes within 1 year postoperatively than patients not on chronic anticoagulation. Further studies are needed to validate these findings and to identify sources of the increased risk of complications in this population, as well as identify factors that may mitigate this risk.